Unveiling the Magical Realism of Pakistan: A Thematic Analysis of A Firefly in the Dark and Midnight Doorways - Khalid, Hajra (Al-Qanṭara, 2024)
Academic scholarship on Magical Realism has focused majorly on Latin America and, later, on other nations around the world, Pakistani Magic realist literature, however, has not garnered enough scholarly attention. The irreal has long been a part of Pakistani oral and literary tradition, especially in Urdu literature (Kanwal and Mansoor 2021). Recently, Pakistani Anglophone writers have started experimenting with the genre of Speculative fiction by appropriating local folklore and mythological worlds and motifs inspired by the Islamic and South Asian civilizations. To generate an understanding of the use of magical realism in Pakistani literature, this study has analyzed two contemporary Pakistani Magic Realist texts, Malik (2021) and Haider (2018). Through closed reading and thematic coding the data was coded into descriptive categories. The study first evaluated the selected texts by analyzing the narrative strategies through which the magical had been integrated with realism in the narrative. The study also mapped the origin of the sources of magical tropes employed by both writers and the distinct reflection of Pakistani customs and norms embedded with the marvellous. This study contributed towards the localization of the genre of Magic Realism to the geolocation of Pakistan by establishing the distinctness of Pakistani Magic realist works.